Post-discharge compliance to venous thromboembolism prophylaxis in high-risk orthopaedic surgery - Bergqvist, David; Arcelus, Juan I.; Felicissimo, Paulo; for the ETHOS investigators (Thrombosis and Haemostasis, 2012)
Venous thromboembolism (VTE) risk persists for several weeks following high-risk orthopaedic surgery (HROS). The ETHOS registry evaluated post-operative VTE prophylaxis prescribed, and actual VTE prophylaxis received, compared with the 2004 American College of Chest Physicians (ACCP) guidelines in HROS patients. We performed a subanalysis of ETHOS to assess patient compliance with ACCP-adherent prophylaxis after discharge and the factors predicting poor compliance. Consecutive patients undergoing hip fracture surgery, total hip arthroplasty, or knee arthroplasty were enrolled at discharge from 161 centres in 17 European countries if they had received adequate in-hospital VTE prophylaxis. Data on prescribed and actual prophylaxis received were obtained from hospital charts and patient post-discharge diaries. Good compliance was defined as percentage treatment intake ≥80% with no more than two consecutive days without treatment. A total of 3,484 patients (79.4%) received ACCP-adherent anticoagulant prescription at discharge and 2,999 (86.0%) had an evaluable patient diary. In total, 87.7% of evaluable patients were compliant with prescribed treatment after discharge. The most common reason for non-compliance (33.4%) was “drug was not bought”. Injection of treatment was not a barrier to good compliance. Main factors affecting compliance related to purchase of and access to treatment, patient education, the person responsible for administering injections, country, and type of hospital ward at discharge. Within our study population, patient compliance with ACCP-adherent thromboprophylaxis prescribed at discharge was good. Improvements in patient education and prescribing practices at discharge may be important in further raising compliance levels in high-risk orthopaedic surgery patients.
Keywords: Compliance; ETHOS registry; orthopaedic surgery; post-discharge venous thromboembolism prophylaxis